Scaling the Andean Shilajit: A Novel Neuroprotective Agent for Alzheimer’S Disease - Santander-Meyer, R; Rojo-Castillo, L; Pastor-Jiménez, M; Wong-Guerra, M (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Alzheimer’s disease (AD) is a multifactorial neurodegenerative disorder without a cure, despite the enormous number of investigations and therapeutic approaches. AD is a consequence of microglial responses to “damage signals”, such as aggregated tau oligomers, which trigger a neuro-inflammatory reaction, promoting the misfolding of cytoskeleton structure. Since AD is the most prevalent cause of dementia in the elderly (>60 years old), new treatments are essential to improve the well-being of affected subjects. The pharmaceutical industry has not developed new drugs with efficacy for controlling AD. In this context, major attention has been given to nutraceuticals and novel bioactive compounds, such as molecules from the Andean Shilajit (AnSh), obtained from the Andes of Chile. Primary cultures of rat hippocampal neurons and mouse neuroblastoma cells were evaluated to examine the functional and neuroprotective role of different AnSh fractions. Our findings show that AnSh fractions increase the number and length of neuronal processes at a differential dose. All fractions were viable in neurons. The AnSh fractions inhibit tau self-aggregation after 10 days of treatment. Finally, we identified two candidate molecules in M3 fractions assayed by UPLC/MS. Our research points to a novel AnSh-derived fraction that is helpful in AD. Intensive work toward elucidation of the molecular mechanisms is being carried out. AnSh is an alternative for AD treatment or as a coadjuvant for an effective treatment. © 2023 by the authors.